Comparative Study Regarding the Adherence to the Mediterranean Diet Among Older Adults Living in Lebanon and Syria - Karam, Joanne; Serhan, Carole; Swaidan, Eman; Serhan, Mireille (Frontiers in Nutrition, 2022)
The Mediterranean diet (MedDiet) has been associated with many health benefits. Poor adherence to MedDiet has been found among Lebanese adults, while in Syria, little is known about the adherence to MedDiet. A quantitative research approach was used, and data were collected through convenience sampling. The structure of the survey included the socio-economic and demographic data and the validated 14-point MedDiet assessment tool. The target population included 367 Lebanese and Syrian adults respectively residing in Lebanon and Syria. Descriptive statistics were used to explore the characteristics of the sample population. Adequate adherence MedDiet was determined if the Med-Diet score ≥ 9. Significant differences among the variables and the adherence to the MedDiet were examined using the chi-square test. Approximately 47.42% of participants reported adherence to MedDiet higher than 9, with a mean of 7.98. Lebanese participants, men, and those who are aged between 64 and 67, had higher adherence than Syrian participants, women, and other age groups, respectively. Lebanese participants (7.82 ± 2.32) had slightly higher adherence than Syrian participants (7.31 ± 2.04). Wine, sofrito, vegetables, and olive oil were mostly consumed by participants, with differences in consumption between the Lebanese and Syrian adults. The statistical analysis performed using the chi-square test showed no statistical difference (P>.05) between Lebanese and Syrian participants regarding their consumption of 160 red meat, butter/margarine, and sugary drinks. Future studies in the aged population are required to explore furthermore the adherence to MedDiet in Lebanon and Syria and its impact on health.